Epidemiology of HEV Infection in Blood Donors in Southern Switzerland - Fontana, Stefano; Ripellino, Paolo; Niederhauser, Christoph; Widmer, Nadja; Gowland, Peter; Petrini, Orlando; Aprile, Manuela; Merlani, Giorgio; Bihl, Florian (Microorganisms (Basel), 2023)
From 2014 to 2016, the number of hepatitis E virus (HEV) infections in southern Switzerland increased dramatically and suggested food as a potential infection reservoir. We evaluated the effects of food control measures introduced to limit HEV infections, assessing anti-HEV IgG and IgM rates in blood donors before and after the implementation of food control measures in 2017. From 2012 to 2013, we screened 1283, and from 2017 to 2019, we screened 1447 donors for IgG and IgM antibodies. No statistically significant differences were detected for IgG (32.8% from 2012 to 2013 vs. 31.1% from 2017 to 2019, p = 0.337) or IgM rates (2.0% from 2012 to 2013 vs. 2.8% from 2017 to 2019, p = 0.21). Rural provenience and age > 66 are predictors for positive IgG serology. A total of 5.9% of 303 donors included in both groups lost IgG positivity. We also determined nucleic acid testing (NAT) rates after the introduction of this test in 2018, comparing 49,345 donation results from southern Switzerland with those of 625,559 Swiss donor controls, and only 9 NAT-positive donors were found from 2018 to 2023. The high HEV seroprevalence in southern Switzerland may depend on different food supply chains in rural and urban areas. Local preventive measures probably have a limited impact on blood HEV risk; thus, continuous NAT testing is recommended.